2020
DOI: 10.1002/ygh2.380
|View full text |Cite
|
Sign up to set email alerts
|

Baseline quantitative histology in therapeutics trials reveals villus atrophy in most patients with coeliac disease who appear well controlled on gluten‐free diet

Abstract: Summary Background The prevalence and severity of duodenal injury in coeliac disease patients controlled on a gluten‐free diet is unclear. Aims To use quantitative histology to assess duodenal injury in treated coeliac disease. Methods Quantitative histology in pre‐treatment duodenal biopsies collected in clinical trials assessing an investigational immunotherapy for coeliac disease was analysed. Morphometric readings were converted to Marsh classifications. Results Ninety‐three patients had duodenal biopsies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 22 publications
(44 reference statements)
1
50
2
Order By: Relevance
“…analysis showed GFD treated patients had deregulated pathways and showed distinct combined overall biological pathway profile from the "healthy" pathway status observed in gluten exposed HLA-DQ2+ healthy controls. This result is consistent with recent reports of Sangineto et al (48) who have showed constitutive changes in CD PBMC despite long-term GFD treatment, albeit compared to non-DQ2+ healthy controls, and A.James et al (49) who have showed that majority of long-term GFD treated CD patients have persistent villous atrophy despite being seronegative for transglutaminase antibodies. Glutathione is an antioxidant and its proper production and levels are necessary in CD as oxidative stress is a major feature in CD intestinal lesions.…”
Section: Discussionsupporting
confidence: 92%
“…analysis showed GFD treated patients had deregulated pathways and showed distinct combined overall biological pathway profile from the "healthy" pathway status observed in gluten exposed HLA-DQ2+ healthy controls. This result is consistent with recent reports of Sangineto et al (48) who have showed constitutive changes in CD PBMC despite long-term GFD treatment, albeit compared to non-DQ2+ healthy controls, and A.James et al (49) who have showed that majority of long-term GFD treated CD patients have persistent villous atrophy despite being seronegative for transglutaminase antibodies. Glutathione is an antioxidant and its proper production and levels are necessary in CD as oxidative stress is a major feature in CD intestinal lesions.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, quantitative histology with well-oriented biopsy sections was shown to reveal villus atrophy in the majority of patients with celiac disease compliant with well-controlled GFDs. 39 The celiac disease patients in the present study did not reach a duodenal mucosal healing described as fully normal. 40 Even if our 6 control patients without evidence of celiac disease had morphologically similar small intestinal mucosal findings, they clearly differed from celiac disease patients on a GFD as related to the transcriptomic findings.…”
Section: Discussioncontrasting
confidence: 55%
“… 13 , 21 , 24 , 62 These methods were also adopted in recent clinical drug and vaccine trials. 22 , 23 , 39 In the present study, we show that the expression of a selected subset of protein-coding genes correlates extremely well with the extent of morphological damage and inflammation in control patients and celiac disease patients on a GFD before and after the gluten challenge (presented as heatmaps in the order of VH:CrD and IEL density in Figure 10 ). It should be noted that the RNA was extracted from separate cuttings but from the same paraffin-embedded biopsy blocks that had been used for morphometry measurements, thus avoiding the patchy lesion pitfalls observed between biopsies in short gluten challenges using low and moderate amounts of gluten.…”
Section: Discussionmentioning
confidence: 57%
“…13,21,24,28 These methods were also adopted in recent clinical drug/vaccine trials. 22,23,48 In the present study, we show that the expression of a selected subset of protein-coding genes correlates extremely well with the extent of morphological damage and inflammation in control patients and celiac disease patients on a GFD before and after the gluten challenge (presented as heat maps in the order of VH:CrD and IEL density, supplementary figure S2). It should be noted that the RNA was extracted from separate cuttings but from the same paraffin-embedded biopsy blocks that had been used for morphometry measurements, thus avoiding the patchy lesion pitfalls observed between biopsies in short gluten challenges using low and moderate amounts of gluten.…”
Section: Discussionmentioning
confidence: 56%